Improvement of Structural and Optical Properties of ZnO1-xAgOx Nano Composite Thin Film Using Pulsed Laser Deposition - Husain , Safaa E.; Abbas, Lamia K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2026)
Thin films of ZnO1-xAgOx nanostructures were successfully deposited on glass substrates using pulsed laser deposition with varying AgO nanoparticle concentrations. Structural and optical characterizations were performed to evaluate the effect of AgO incorporation. XRD patterns confirmed a hexagonal polycrystalline structure, with additional peaks for cubic silver or silver oxide due to AgO inclusion. Crystal size slightly increased at x = 0.05 and 0.25, indicating enhanced growth, while it decreased at other ratios due to lattice strain and defects. FTIR analysis showed Zn–O stretching modes, hydroxyl, carbon-based groups, and Ag–O bands, confirming successful incorporation. AFM results revealed reduced surface roughness with low AgO ratios, followed by increased roughness at x = 0.25 and 0.30. Optical transmittance decreased, while absorption increased with AgO, and the optical band gap narrowed from 3.2 eV to 2.2 eV. Hall Effect measurements indicated reduced n-type carrier concentration, suggesting a shift toward p-type conductivity via acceptor level formation.